2019
DOI: 10.3390/biom9030107
|View full text |Cite
|
Sign up to set email alerts
|

Association of MMP9-1562C/T and MMP13-77A/G Polymorphisms with Non-Small Cell Lung Cancer in Southern Chinese Population

Abstract: Background: Matrix metalloproteinases (MMPs) are capable of degrading and modifying most components of the extracellular matrix (ECM) and the basal membrane (BM), and play crucial roles in cancer invasion and metastasis. MMP gene expressions were regulated primarily at the transcriptional level, which was associated with tumor spread and patient prognosis. Polymorphisms in MMPs have been reported to be associated with non-small cell lung cancer (NSCLC). The objective of this study aim to evaluate the serum lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 29 publications
(47 reference statements)
5
63
0
Order By: Relevance
“…In this study, we found ASA VI promoted the transcriptional expression of PPAR-γ gene in LPS-treated microglia. Simultaneously, ASA VI promotes nuclear transfer of PPAR-γ in LPS-induced microglia ( Gao et al, 2017 , Gao et al, 2017 , Gao et al, 2017 , Li et al, 2019 ). These data indicated that ASA VI activated the PPAR-γ signaling pathway in LPS-induced microglia.…”
Section: Discussionmentioning
confidence: 98%
“…In this study, we found ASA VI promoted the transcriptional expression of PPAR-γ gene in LPS-treated microglia. Simultaneously, ASA VI promotes nuclear transfer of PPAR-γ in LPS-induced microglia ( Gao et al, 2017 , Gao et al, 2017 , Gao et al, 2017 , Li et al, 2019 ). These data indicated that ASA VI activated the PPAR-γ signaling pathway in LPS-induced microglia.…”
Section: Discussionmentioning
confidence: 98%
“…Intestinal microbiome is “the second genome” of human. The disturbance of intestinal microorganisms can directly influence immune system, especially inflammatory diseases and autoimmune diseases ( Li et al, 2019 ). Therefore, although genetic factors are proved to be vital to the occurrence of SLE, environmental factors are also highly correlated to SLE.…”
Section: Discussionmentioning
confidence: 99%
“…In the cosmetics industry, it is currently being used as facial masks or ointments and also in food products, accompanied with other components to treat skin disease as well as help in activation of blood circulation [3]. Presently, the replacement of synthetic antioxidant with naturally occurring antioxidant is increasing due to the side effects associated with synthetic antioxidant such as increased risk of cancer [4][5][6][7][8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%